2014
DOI: 10.1590/0001-3765201495912
|View full text |Cite
|
Sign up to set email alerts
|

Different slopes of a mountain can determine the structure of ferns and lycophytes communities in a tropical forest of Brazil

Abstract: A community of Ferns and Lycophytes was investigated by comparing the occurrence of species on different slopes of a paleoisland in Southeastern Brazil. Our goal was to evaluate the hypothesis that slopes with different geographic orientations determine a differentiation of Atlantic Forest ferns and lycophytes community. We recorded these plants at slopes turned towards the continent and at slopes turned towards the open sea. Analysis consisted of a preliminary assessment on fern beta diversity, a Non Metric M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Also, species richness and abundance of pteridophytes are greater in shady forests than in more open ones or in open vegetation types because there are more shade tolerant species (umbrophiles) of pteridophytes than pioneers/ heliophiles (Tryon & Tryon 1982, Della 2016). Chen et al (2014), Daly et al (2006), Das et al (2013), Della (2016), Dzwonko & Kornas (1994), Eisner & Peterson (1998), Gamarra et al (2003), Gehrig-Downie et al (2012), Goebel et al (2006), Goforth (2006), Granville (1984), Guarino et al (2012), Guimarães et al (2014), Halme & Bodmer (2007), Haq et al (2017), Hemp (2002), Hernández et al (2013), Higgins et al (2011), Johns (1985, Karst et al (2005), Kessler (2001), Kessler & Bach (1999), Khwaiphan & Boonkerd (2008), Klinka et al (1989), Loschi et al (2010), Medeanic et al (2016), Nettesheim et al (2014), Nóbrega et al (2011), Norton (1994, Page (2002), Patil et al (2016), Pos & Sleegers (2010), Ranieri (2015), Richard et al (2000), Richardson & Walker (2010), Rocha-Uriartt et al (2016), Ruokolaine...…”
Section: Methodsmentioning
confidence: 99%
“…Also, species richness and abundance of pteridophytes are greater in shady forests than in more open ones or in open vegetation types because there are more shade tolerant species (umbrophiles) of pteridophytes than pioneers/ heliophiles (Tryon & Tryon 1982, Della 2016). Chen et al (2014), Daly et al (2006), Das et al (2013), Della (2016), Dzwonko & Kornas (1994), Eisner & Peterson (1998), Gamarra et al (2003), Gehrig-Downie et al (2012), Goebel et al (2006), Goforth (2006), Granville (1984), Guarino et al (2012), Guimarães et al (2014), Halme & Bodmer (2007), Haq et al (2017), Hemp (2002), Hernández et al (2013), Higgins et al (2011), Johns (1985, Karst et al (2005), Kessler (2001), Kessler & Bach (1999), Khwaiphan & Boonkerd (2008), Klinka et al (1989), Loschi et al (2010), Medeanic et al (2016), Nettesheim et al (2014), Nóbrega et al (2011), Norton (1994, Page (2002), Patil et al (2016), Pos & Sleegers (2010), Ranieri (2015), Richard et al (2000), Richardson & Walker (2010), Rocha-Uriartt et al (2016), Ruokolaine...…”
Section: Methodsmentioning
confidence: 99%
“…Souza 2013). Such studies have revealed that environmental factors can positively or negatively influence the presence of species (Finger and Filho 2014) and several have addressed the extent to which floristic composition depends on abiotic versus biotic processes, such as dispersal limitations and biological interactions (Hubbell 2001;Dalling et al 2002;Wyatt and Silman 2004;Nettesheim et al 2014). As discussed by Webb et al (2002), the relationship between a species and spatial/environmental variables is the result of long evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…The type of environmental variables showed that precipitation contributed the most to the distribution prediction, followed by temperature, and topographic contribution the least. Topographic variables may affect the distribution of plants over a smal-scale landscape, but on a large scale, they may be minimal, the reason could be that topographic variables exert their influences on plants indirectly (Vormisto et al, 2004;Nettesheim et al, 2014). The high habitat suitability areas have comparatively more precipitation and with less fluctuation in the driest quarter, but very low habitat suitability areas showed the opposite tendency.…”
Section: The Impact Of Chief Variables On Natural Distributionmentioning
confidence: 99%